Experience the use of phytopreparations Cyclodynon® in patients with insufficiency of corpus luteum and hyperprolactinemia - Сметник, В. П.; Бутарева, Л. Б. (REPRODUCTIVE ENDOCRINOLOGY, 2015)
Complex clinical and laboratory examination among 20 patients aged 25 to 41 years with relative hyperprolactinemia suffering from menstrual irregularities of various kinds was performed. The control group consisted of 15 healthy women. In patients with corpus luteum insufficiency, caused by hyperprolactinemia, in order to correct existing disorders phytopreparation agnucaston (Cyclodynon®) was used. The results showed that agnucaston (Cyclodynon®) effectively reduced the increased secretion of prolactin, the drug increases cyclic secretion of progesterone in the luteal phase of the cycle, which helps normalize the menstrual rhythm. The authors concluded that agnucaston (Cyclodynon®) can be considered an alternative to treatment with other stimulators of dopamine receptors in their intolerance in patients with hyperprolactinemia of non-tumor genesis.